PHYSICAL CHARACTERISTICS OF 70 SPRINGS IN GALLAOROL DISTRICT (JIZZAKH REGION, UZBEKISTAN) - S. A. Tashpulatova; O. M. Mamarakhimov (Web of Journals Publishing, 2023)
Samples were taken from 70 springs in Gallaorol district, Jizzakh region of Uzbekistan, and their physical properties (smell, color level, turbidity, precipitation, clarity) were checked in the water laboratory.
Keywords: Physical properties of spring water, Jizzakh, Gallaorol, spring waters, smell, color level, turbidity, precipitation, clarity.